First Gambian Ricinulei (Arachnida: Ricinoididae): northernmost African record for the order - Penney, David; Marusik, Yuri; Wheater, C. Philip; Langan, A. Mark (Zootaxa, 2009)
Ricinulei is an arachnid order of great antiquity with fossils of the extinct families Curculioididae and Poliocheridae known from the Pennsylvanian (c. 300Ma) of Europe and North America (Selden 1992). However, extant species (Ricinoididae) are known only from Africa (Ricinoides) and South and Central America (Cryptocellus and Pseudocellus), with species of the latter genus extending northwards to Mexico and Texas (Naskrecki 2008).